The importance of being Aeolian: shaping Aeolian identity in ancient Asia Minor - Apostolou, Stefanos (2018)
This thesis examines the formation of Aeolian collective identity in Asia Minor from the Archaic to the Roman period, and the connection of the predominant foundation myth, the Aeolian migration, to other foundation myths, which mainly involved Amazons. I intend to explore the dynamic interaction between geography and foundation myths of Aeolian poleis. When foundation myths are examined in light of the actual conditions on the ground, in a context of territorial conflicts, their function not only as a basis of co-belonging, but also in support of territorial claims against other contesters, becomes apparent. The thesis also examines both public knowledge and perceptions of Aeolis as a geographical space by ancient authors to determine what authors and political authorities expected their audience to understand by terms such as ‘Aeolian’, ‘Aeolians’, and ‘Aeolis’. I argue that the localisation of Troy on the north-west corner of Asia Minor in the 5th century created a focal point for the previously vague Homeric Troy. For this reason, the area and conceptual boundaries of Aeolis expanded onto the southern coast of the Troad, and resulted in different geographical accounts of Aeolis in ancient authors. In the same way that Aeolis was not the same region throughout antiquity, neither were the Aeolians. The Aeolian migration allegedly brought diverse groups from mainland Greece to Asia Minor. I re-evaluate the myth in its literary context, as a development of the recurring theme of ‘kings from abroad’. From its initial function as means to differentiate elites (‘from abroad’) from non-elites, the myth was diffused and embraced the entire Greek population of the area. The etymology and meaning of the word ‘Aeolians’ (= the diverse, the polyglots), indicates that it was initially an etic name given by outsiders, which was internalised at a later stage by communities in Aeolis and was recast as a marker of co-belonging based on diversity in opposition to the ‘homogenous locals’.